An innovative solution for T‐tube obstruction: The tracheostomy–customized stent combination. (14th December 2017) - Mehta, Ravindra M.; Singla, Abhinav; Bhat, Rajani S.; Rao, Rasika; Agarwal, Ritesh
Abstract : The Montgomery T‐tube (MTT) is a useful tool for post‐tracheostomy tracheal stenosis. However, MTTs can get blocked. We present a case series of life‐threatening MTT blockage, wherein a split‐function option was implemented, which was a customized silicone Dumon stent above the tracheostomy to maintain both airway and phonation. This tracheostomy–customized stent combination serves the same function as an MTT, with a greater margin of safety due to the easy suctioning capacity of the tracheostomy. With a fenestrated tracheostomy and stent above, speech is effectively preserved. We recommend this strategy in severe MTT blockage as a superior option to regular tracheostomy. Laryngoscope, 1795–1797, 2018